Comparative Study of Children's Attitudes to Learning Environment - Jonynienė, Živilė; Teresevičienė, Margarita (Acta Paedagogica Vilnensia, 2003)
The purpose of the research is to analyse the children's attitudes to learning environment in a comparative aspect. The contemporary concept of good learning includes 1) the context of learning, 2) learner's initiative, goals and 3) the co-operation of all participants of the learning process. The opinion of students about their rights in school and in the learning process reflects the real situation: i.e., the situation as perceived by students. In order to work according to the imperatives of the concept good learning, it is crucial to take into consideration students' opinions and to evaluate the situation consistently with the evaluation that students complete. The attitudes of children of various ages (aged 7-9, 12-14, 16-18) and adults (teachers, parents, others) with regard to the rights children have and the rights they need to have were obtained by a questionnaire procedure carried out in Lithuania and Sweden, in 1998. Closed type of questionnaires was used, which enabled the researchers to process a quantitative analysis of attitudes held by children and adults. Respondents: 1225 secondary school students in Lithuania and 178 in Sweden; 293 adults in Lithuania and 37 in Sweden. Also, children (133 in Lithuania and 124 in Sweden) were asked to respond to open questions regarding the most important rights at school, discrimination and equality with teachers. For the quantitative analyses standard questionnaires of the international study of children's rights were used. The international project mentioned is the research project initiated the ISPA International School Psychology Association. Students in schools lack the respect of their opinions, the possibility to be with people who love and take care of them and emotional security. For students in Sweden the most important question in the educational process is the right to influence decision making. They want an active position. For Lithuanian students the respect of their opinion, physical and emotional security and support was more important. These learning conditions and quality of studies, together with the professionalism of teachers and fair evaluation reflect the nature of attitude of Lithuanian students to learning and their orientation towards knowledge. 75 % students in Lithuania and 60 % students in Sweden think that relations between students and teachers are unequal, because teachers are always "right", they "decide everything". In this situation, co-operation of the participants in the learning process is difficult and often there is no co-operation or just the rhetoric. In Lithuania one third of students (32%) said that they do not receive or rarely receive feedback and explanations about their evaluations and marks; 66% of 12-18 years old students rarely or never feel emotional security; students think that physical environment is not safe enough at school. The lack of emotional and physical security, limitations for Jearner’s activities, disrespect for student's opinions, unequal relations between students and teachers, confusing evaluation procedures all show the discrepancy between the children's situation in society and in school as described in various legal documents, and in reality. The potentials of developing one's personality are prevented from their full development, and favourable social-psychological conditions for learning are not created because of these discrepancies.
Keywords: school; context of learning; learning environment; children's rights